(untitled) (Perioperaciina Medicina, 2023)
Considering the high frequency of degenerative-dystrophic diseases of the joints and the constant growth of morbidity, the improvement of treatment conservative approaches is an urgent task of modern medicine. Background: to evaluate the effectiveness of using Artro-Patch (3 % hyaluronic acid solution, 3 ml) in patients with stage II knee osteoarthritis and the need to perform preliminary aspiration of arthritic fluid before intraarticular injection. Materials and methods. 60 patients with stage II knee osteoarthritis who were treated with the use of Artro-Patch (3 % hyaluronic acid solution, 3 ml) were examined. The average age is 45.56 ± 8.61 years. The group includes 38 (63.33 %) women and 22 (36.67 %) men. Among them 2 groups were formed. Patients of group 1 (n = 30) received intra-articular injection of Artro-Patch. Patients of group 2 (n = 30) were injected with Artro-Patch with prior aspiration of arthritic synovial fluid. Clinical outcomes were assessed using the WOMAC questionnaire at admission, 30 days, and 90 days after the procedure. The StatSoft STATISTICA 13 program was used for statistical analysis. The probability of an error-free forecast was set at p < 0.05. Results. As a result of using Artro-Patch in patients with stage II knee osteoarthritis, it was possible to achieve a reliable improvement of all clinical indicators determined by the WOMAC questionnaire. It has been proven that performing a preliminary aspira-tion of arthritic fluid before intra-articular injection of Artro-Patch leads to the development of a more stable and better clinical result at 30 days, with subsequent positive dynamics up to 90 days of observation. Conclusions. Thus, the high effectiveness of using Artro-Patch drug in the treatment of stage II knee osteoarthritis has been proven. To achieve a stable and better clinical result, it is recommended to perform a preliminary aspiration of arthritic fluid before intra-articular injection of the drug.